Exploring Constraints of Business Productivity in a Province Nearby the Country Capital: The Case of the UK and Vietnam - Brown, Christopher; Giang, Nguyen Thuc Huong; Huong, Tran Thi (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 36 No 5E, 2020)
In the digital era, the socio-economic and technological environment is changing continuously. Business productivity is becoming a more and more significant issue in the economy and it is essential to find out what motivates and limits productivity. The inequality in economic development of different provinces in each country is getting higher priority of government in both developed and developing countries. In this comparative study, we chose Hertfordshire in UK and Hung Yen in Vietnam, two provinces nearby the capitals of those countries respectively. These provinces have similar geographic characteristics and types of business structure. The study explores the constraints of business productivity. Hung Yen, one of Hanoi's nearby provinces, enjoys spillover benefits from the capital city's development. However, Hung Yen has to face many challenges from its geographical location and a shortage of high-quality human resources (people who tend to work and develop their careers in the capital). The same as Hung Yen, in the UK Hertfordshire is a county adjacent to London and suffers the same challenges related to graduate skills’ mobility and productivity gaps in the STEM skilled sectors. The correlation in business development issues between Hertfordshire and London is similar to the one between Hung Yen and Hanoi, in growth, hard-to-fill skills vacancies and productivity. In recent years, Hertfordshire has had numerous achievements in economic development and improved productivity growth. Therefore, the authors have focused on enterprises in these two provinces with their influencing/constraining productivity factors, including: i) innovation and technology through product/service launches; ii) workforce skill gaps; iii) leadership and management constraints; and iv) business constraints. From that, we propose some recommendations to foster business productivity of enterprises located in the two provinces.